The Use Of The Profiling Method In The Investigation Of Criminal Offenses Related To Air Transport Security Breaches - Podzolkova, Tetiana (Archives of Criminology and Forensic Sciences, 2022)
This scientific article is devoted to the study of the problem of air transport security and the investigation of crimes related to its violation. Crimes related to air transport security can have serious consequences and threaten people’s lives. The authors of the article note that effective investigation and identification of criminals are crucial in such situations. One of the innovative approaches explored in the article is criminal profiling. This method of crime research is based on the analysis of behavioral, psychological and other characteristics of criminals. The use of criminal profiling can be extremely valuable in the investigation of criminal offenses aimed at violating air transport security. The article examines the structure of criminal profiling, which consists of three levels of analysis: operational, tactical and strategic. The importance of ensuring the safety of air transport and the need for effective investigation of crimes related to it are emphasized. The use of criminal profiling, in particular through operational, tactical and strategic analysis, can be a valuable tool for the detection and prevention of criminal offenses that threaten the safety of air transport.